Prostaglandin D2 receptor antagonists in early development as potential therapeutic options for asthma. (1st September 2016) - Santus, Pierachille; Radovanovic, Dejan
ABSTRACT: Introduction : Asthma is a chronic inflammatory disease characterized by bronchial hyper-reactivity. Although many currently available treatment regimens are effective, poor symptom control and refractory severe disease still represent major unmet needs. In the last years, numerous molecular therapeutic targets that interfere with the innate inflammatory response in asthma have been identified. Promising preliminary results concern the signaling cascade promoted by prostaglandin D2 (PGD2) and its receptor antagonists. Areas covered : The aim of this review is to provide the most recent clinical and preclinical data on the efficacy and safety of newly developed compounds for the treatment of allergic asthma. The authors will present an overview of the pathogenetic molecular mechanisms sustaining the chronic inflammatory response in asthma; the focus will be then directed on the mediators of the PGD2 pathway, the chemoattractant receptor-homologous molecule expressed on TH2 cells, and their latest antagonists developed. Expert opinion : Bronchodilators and corticosteroids are not sufficient to achieve a satisfactory management of all asthmatic patients; the development of new specific treatments appears therefore essential. The good results in terms of cellular, functional and clinical outcomes, together with an acceptable safety of the CRTh2 antagonists represent a promising start for a tailored management of allergic asthma.